Analysis of IgG4-positive clones in affected organs of IgG4-related disease. Issue 6 (1st November 2016) - Kakuchi, Yasushi; Yamada, Kazunori; Ito, Kiyoaki; Hara, Satoshi; Fujii, Hiroshi; Yamagishi, Masakazu; Kawano, Mitsuhiro
Abstract: Objective : We investigated class switch reaction (CSR) in affected organs and evaluated whether the same or genetically related clones exist in IgG4-RD. Methods : We studied three patients with IgG4-RD. Total cellular RNA was extracted from salivary glands and peripheral blood and lung tissue. Activation-induced cytidine deaminase (AID) and immunoglobulin heavy chain third complementarity determining region (IgVH-CDR3) of IgM and IgG4 were detected by reverse transcription polymerase chain reaction (RT-PCR). We analyzed the clonal relationship of infiltrating IgG4-positive cells, as compared with IgM. We determined the existence of common clones among organs and patients. Result : AID was expressed in salivary glands of all patients and lung tissue in one. Closely related IgVH-CDR3 sequences in infiltrating IgG4-positive cells were detected in salivary glands and lung tissue. Identical IgVH-CDR3 sequence between IgM and IgG4 in salivary glands was detected in one patient, indicating CSR in salivary glands. Identical IgVH-CDR3 sequences of IgG4-positive cells were detected between salivary glands and peripheral blood in two patients. Four identical sequences of IgVH-CDR3 existed between patients. Interestingly, one of the four sequences was detected in all patients. Conclusion : Our results demonstrate the existence of common antigen(s) shared by patients with IgG4-RD.